Raziskovalne metode v folkloristiki - med tradicionalnim in inovativnim - Golež Kaučič, Marjetka (Traditiones (Ljubljana), 2001)
The paper focuses on traditional and innovative methods in Slovene folkloristics. It tries to shematize these methods as they occured in the course of the development of this science, and arrange them according to the subject of their research. It emphasizes interdisciplinary cooperation, but also draws attention to specific characteristics of folkloristic methodology. Folkloristic research methods are aranged according to work hierarchy and according to special aspects of research projects. The author concludes that in contemporary folkloristics, old and new research method are interwoven in avery distinctive manner
Keywords: ethnology; etnologija; folkloristics; folkloristika; Slovenia; Slovenija; raziskovalno delo